The Role of Personality Traits and Decision-Making Styles in Career Decision-Making Difficulties - Mine Aydemir Dev; Nuran Bayram Arlı (Behavioral Sciences)
Career decisions are one of the most important decisions individuals make in their lives. These decisions are multifaceted and complex, making them a challenging process, particularly for students. This creates obstacles for students navigating the career choice process. The aim of this study is to examine career decision-making difficulties within the framework of personality traits and decision-making styles. The target group of this study is undergraduate students studying at a public university. For this research, we collected data through online questionnaire forms. The questionnaire comprised demographic questions and three scales: career decision-making difficulties, personality traits, and decision-making styles. A total of 505 students (63.2% female) participated in the questionnaire. The research model was tested using path analysis. We also conducted network analysis in order to better understand and visualize the relationships between the sub-dimensions of the scales. The findings showed significant direct relationships between career decision-making difficulties and personality traits (conscientiousness, openness, neuroticism, and agreeableness) and decision-making styles (rational, dependent, avoidant, and spontaneous). According to the path analysis result, neurotic personality traits were positively correlated with career decision-making difficulties, while openness to experience, agreeableness, and conscientiousness were negatively correlated with them. The relationship between dependent, avoidant, and spontaneous decision-making styles and career decision-making difficulties was positive. These results provide valuable insights into the factors that shape career decisions, helping students make more informed choices and manage their career paths effectively.